The Future of AI in Academic Writing: A Case Study of Undergraduate and Postgraduate Assessments - Dr. Shahid Rafiq; Aqsa Nawaz; Dr. Ayesha Afzal (Dialogue Social Science Review (DSSR), 2025)
The integration of artificial intelligence (AI) tools in academic writing has gained significant attention globally, yet its implications remain underexplored in developing countries like Pakistan. This qualitative study investigates the role of AI tools in undergraduate and postgraduate assessments within the Pakistani academic context, focusing on their perceived benefits, challenges, and implications. Using thematic analysis, the study draws insights from semi-structured interviews with students and educators from various universities in Pakistan. The findings reveal that AI tools enhance efficiency and writing quality while addressing language-related challenges, particularly for students with limited English proficiency. However, ethical concerns, including plagiarism and over-reliance on AI, alongside socio-economic barriers such as unequal access to digital tools, hinder their effective utilization. Additionally, the absence of institutional policies and training programs exacerbates these challenges, creating uncertainty regarding AI integration in academic settings. This research highlights the need for comprehensive frameworks, equitable access to resources, and ethical guidelines to ensure the responsible use of AI tools in education. By contextualizing global trends within Pakistan’s socio-economic and educational landscape, this study provides valuable recommendations for policymakers and educators to navigate the evolving role of AI in academic writing.